Dispersal and dilution of wastewater from an ocean outfall at Davis Station, Antarctica, and resulting environmental contamination. (June 2016) - Stark, Jonathan S.; Bridgen, Phil; Dunshea, Glenn; Galton-Fenzi, Ben; Hunter, John; Johnstone, Glenn; King, Catherine; Leeming, Rhys; Palmer, Anne; Smith, James; Snape, Ian; Stark, Scott; et al.
Abstract: The Antarctic Treaty permits the discharge of wastewater into Antarctic marine waters providing that conditions exist for initial dilution and rapid dispersal. We investigated the dilution and dispersal of macerated wastewater around Australia's Davis Station in East Antarctica and examined sediments for evidence of contaminants. Methods used to examine hydrodynamic conditions included current meters, dye release experiments and measurement of sewage-associated microbial markers and surfactants in the water column. We measured marine sediments for metals, nutrients, PBDEs, hydrocarbons and faecal sterols. We propose that if there is adequate dilution and dispersal there would be no significant difference in contaminant concentrations in sediments around the outfall compared to distant control sites. Currents were strongly correlated with prevailing wind conditions. Modelling indicated that diffusivity of wastewater had the greatest effect on dilution factors and that neither discharge rates nor local currents had as much effect. During summer conditions of open water, wastewater is likely to be constrained in a narrow plume close to the coast. Concentrations of sewage bacteria were high around the outfall and detected up to 1.5 km away, along with dye. There were significant differences in sediment concentrations of metals, PBDEs, hydrocarbons, nutrients and faecal sterols between sites within 2 km of the outfall and control sites. We conclude that dilution and dispersal conditions at the Davis outfall are insufficient to prevent the accumulation of contaminants in local sediments and that microbial hazards posed by wastewater are an environmental risk to local wildlife. Highlights: Effluent is likely to be constrained in a narrow plume very close to the coast. Sewage bacteria were in high concs. around the outfall and found up to 1.5 km away. Metals, PBDEs, hydrocarbons and faecal sterols were detected up to 2 km away. Dispersal and degradation were insufficient to prevent accumulation of contaminants. Microbial contamination poses an environmental risk to local wildlife.